Red Rooms, Water Enclosures and Other Unfolding Spaces - Lauretta Vinciarelli (Oz, 1995)
The architectural space that I have painted since 1987 does not portray solutions to specific demands of use, it is not the space of a project; at least not a project as the rational answer to a program. Rather, this space is the outcome of a mental process, that unfolds itself in images and resists verbalization.